The impact of academic stress on the dietary behaviour of female undergraduates in Kingdom of Saudi Arabia - Mansoury, Manal (2016)
There is a paucity of research into the effect of stress on the dietary behaviour of undergraduate students in non-western societies, particularly middle-eastern countries. This is in spite of the seeming importance of culture and ethnicity as potential moderating factors of the stress- diet relationship. Consequently, there is limited knowledge and understanding of the factors that influence the stress-diet relationship in these societies. The aim of this study was to investigate the effect of academic stress on the dietary behaviour of female undergraduate students in King Abdul-Aziz University in Saudi Arabia and how it is influenced by the lifestyle choices and coping strategies adopted by students. A longitudinal survey of a convenient sample of undergraduate students was carried out using several instruments. These included a self-completed questionnaire (to collect data on socio-demographics, lifestyle choices), Perceived Stress Scale (PSS14), Brief COPE instrument, and 24hour recall interviews. Data were collected when no examinations were scheduled (T1), and again during examinations (T2). The participants were drawn from the female undergraduate student population in six different faculties at the university with a median age of 21.6 years. 491 participants were recruited to the study (T1), of whom 322 completed the follow-up study (T2) during the examination period. The results showed that students reported significantly higher levels of stress during examinations (p<0.001) and that age and smoking were the two discriminating factors of students’ perception of stress. The analysis of food data revealed that there wasn’t a significant difference in the nutrient intake of students during (T1) and (T2). Nonetheless, results showed that during examinations the frequency of food intake was significantly lower (t(320) = 6.195; p=0.001), as with fast food intake (t(320) = -3.439; p=0.001). Whereas the intake of healthy food by students who reported significantly higher levels of stress decreased significantly. The study results also indicated that students reported significantly higher emotion focused coping scores (t (321) = 4.559; p <0.001) during examinations. The findings from this study corroborate existing evidence linking changes in eating behaviour with the increased use of emotional coping strategies. The research equally identified concerns about body image and weight gain as other possible moderators of changes in the frequency of food intake by students during examinations. The key indicators of these concerns include students stated desire to lose weight, actively taking actions to lose weight, skipping meals and self-reported ideal BMIs less than their current BMI. Future work would be usefully directed towards investigating further the paradox between observed increase in emotional coping and reduced frequency in food intake. The influence the food environment (both availability and cultural values) and its impact on dietary behaviour during high stress periods should be explored further.